Heparin-induced thrombocytopenia: a review of concepts regarding a dangerous adverse drug reaction - Junqueira,Daniela Rezende Garcia (2013)
Heparin is a natural agent with antithrombotic action, commercially available for therapeutic use as unfractionated heparin and low molecular weight heparin. Heparin-induced thrombocytopenia (HIT) is a serious adverse reaction to heparin that promotes antibodymediated platelet activation. HIT is defined as a relative reduction in platelet count of 50% (even when the platelet count at its lowest level is above > 150 x 10(9)/L) occurring within five to 14 days after initiation of the therapy. Thrombocytopenia is the main feature that directs the clinical suspicion of the reaction and the increased risk of thromboembolic complications is the most important and paradoxical consequence. The diagnosis is a delicate issue, and requires a combination of clinical probability and laboratory tests for the detection of platelet activation induced by HIT antibodies. The absolute risk of HIT has been estimated between 1% and 5% under treatment with unfractionated heparin, and less than 1% with low molecular weight heparin. However, high-quality evidence about the risk of HIT from randomized clinical trials is scarce. In addition, information on the frequency of HIT in developing countries is not widely available. This review aims to provide a better understanding of the key features of this reaction and updated information on its frequency to health professionals and other interested parties. Knowledge, familiarity, and access to therapeutic options for the treatment of this adverse reaction are mandatory to minimize the associated risks, improving patient safety.